Reirradiation with intensity-modulated radiotherapy in recurrent head and neck cancer - Zwicker, Felix; Röder, Falk; Hauswald, Henrik; Thieke, Christian; Timke, Carmen; Schlegel, Wolfgang; Debus, Jürgen; Münter, Marc; Huber, Peter E. (Head & neck, 2011)
Background: In this retrospective investigation we analyzed outcome and toxicity after intensity-modulated reirradiation of recurrent head and neck cancer. Methods Thirty-eight patients with local recurrent head and neck cancer were evaluated. The median dose of initial radiotherapy was 61 Gy. Reirradiation was carried out with step-and-shoot intensity-modulated radiotherapy (median dose: 49 Gy). Results Median overall survival was 17 months, and the 1- and 2-year overall survival rates were 63% and 34%. The 1- and 2-year local control rates were 57% and 53%. Distant spread occurred in 34%, and reirradiation induced considerable late toxicity in 21% of the patients. Thirty-two percent showed increased xerostomia after reirradiation. The risk for xerostomia was significantly higher for cumulative mean doses of ≥45 Gy to parotid glands. Considering median cumulative maximum doses of 53 Gy to the spinal cord and 63 Gy to the brainstem, no late toxicities were observed. Conclusions Reirradiation with intensity-modulated radiotherapy in recurrent head and neck cancer is feasible with acceptable toxicity and yields encouraging rates of local control and overall survival. - Methods: Thirty-eight patients with local recurrent head and neck cancer were evaluated. The median dose of initial radiotherapy was 61 Gy. Reirradiation was carried out with step-and-shoot intensity-modulated radiotherapy (median dose: 49 Gy). - Results: Median overall survival was 17 months, and the 1- and 2-year overall survival rates were 63% and 34%. The 1- and 2-year local control rates were 57% and 53%. Distant spread occurred in 34%, and reirradiation induced considerable late toxicity in 21% of the patients. Thirty-two percent showed increased xerostomia after reirradiation. The risk for xerostomia was significantly higher for cumulative mean doses of ≥45 Gy to parotid glands. Considering median cumulative maximum doses of 53 Gy to the spinal cord and 63 Gy to the brainstem, no late toxicities were observed. - Conclusions: Reirradiation with intensity-modulated radiotherapy in recurrent head and neck cancer is feasible with acceptable toxicity and yields encouraging rates of local control and overall survival.
Gesehen am 30.01.2023